Llama nanoantibodies with therapeutic potential against human norovirus diarrhea - Garaicoechea, Lorena Laura (2015)
Noroviruses are a major cause of acute gastroenteritis, but no vaccines or therapeutic drugs are available. Llama-derived single chain antibody fragments (also called VHH) are small, recombinant monoclonal antibodies of 15 kDa with several advantages over conventional antibodies. The aim of this study was to generate recombinant monoclonal VHH specific for the two major norovirus (NoV) genogroups (GI and GII) in order to investigate their potential as immunotherapy for the treatment of NoV diarrhea. To accomplish this objective, two llamas were immunized with either GI.1 (Norwalk-1968) or GII.4 (MD2004) VLPs. After immunization, peripheral blood lymphocytes were collected and used to generate two VHH libraries. Using phage display technology, 10 VHH clones specific for GI.1, and 8 specific for GII.4 were selected for further characterization. All VHH recognized conformational epi-topes in the P domain of the immunizing VP1 capsid protein, with the exception of one GII.4 VHH that recognized a linear P domain epitope. The GI.1 VHHs were highly specific for the immunizing GI.1 genotype, with only one VHH cross-reacting with GI.3 genotype. The GII.4 VHHs reacted with the immunizing GII.4 strain and showed a varying reactivity profile among different GII genotypes. One VHH specific for GI.1 and three specific for GII.4 could block the binding of homologous VLPs to synthetic HBGA carbohydrates, saliva, and pig gastric mucin, and in addition, could inhibit the hemagglutination of red blood cells by homologous VLPs. The ability of Nov-specific VHHs to perform well in these surrogate neutralization assays supports their further development as immunotherapy for NoV treatment and immunoprophylaxis.